Pengasuhan Dan Perlindungan Anak Dalam Perundang-Undangan Keluarga Islam Di Indonesia Dan Negara Islam - Zakky Maulana Hadi (CV. ULIL ALBAB CORP, 2024)
Child care and protection are important aspects of Islamic family law, both in Indonesia and other Islamic countries. In the Indonesian context, regulations regarding child care and protection are regulated in various laws such as the Compilation of Islamic Law (KHI), the Child Protection Law, and the Marriage Law. In Islamic countries, child care is also regulated based on Islamic law with several variations in implementation that are adjusted to the local social, cultural, and political context. This study discusses the comparison between the legal regulations for child care and protection in Indonesia and other Islamic countries. This study uses a qualitative approach with a comparative analysis method to explore the similarities and differences in the protection of children's rights, the role of parents, and state intervention in the context of Islamic families. The results of the study show that although there are similarities in the basic principles of Islamic law regarding child care, the implementation and enforcement of the law vary depending on the policies of each country. In Indonesia, a more moderate and national law-based approach tends to be more prominent, while in some Islamic countries, a more conservative interpretation still applies. This study also identifies challenges and opportunities in strengthening child protection within the framework of Islamic family law, both in Indonesia and other Islamic countries.